DUKUNGAN REKAN KERJA DAN KEPUASAN KERJA: KUNCI TUMBUHNYA SIKAP KEWARGAAN DI TEMPAT KERJA - Wahyudi, Wahyudi; Aryanto, Tossy; Hartarini, Yovita Mumpuni (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
Coworker support is a crucial factor in shaping Organizational Citizenship Behavior (OCB). Meanwhile, job satisfaction reflects employees' positive feelings about their work. This study aims to determine and analyze the influence of coworker support and job satisfaction on organizational citizenship behavior. The study was conducted on PLN ULP Bangsri employees using a census approach, resulting in a sample of 34 employees from the entire population. Data were collected using a questionnaire and analyzed using multiple linear regression to test the partial and simultaneous effects between variables. The analysis showed that coworker support significantly influenced OCD, with a calculated t-value of 5.083 and a significance level of 0.000. Job satisfaction also significantly influenced OCD, with a calculated t-value of 5.828 and a significance level of 0.000. Simultaneously, both had a significant effect on OCD, with a calculated F-value of 22.208 and a significance level of 0.000. The coefficient of determination (R²) of 0.589 indicates that 58.9% of the variation in OCD can be explained by coworker support and job satisfaction. Based on these findings, organizations are advised to continue strengthening coworker support and creating satisfying working conditions to enhance organizational citizenship behavior.